2019
DOI: 10.1111/wvn.12399
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Parenting Interventions on Psychosocial Adjustment in Parents of Children and Adolescents with Type 1 Diabetes: A Meta‐Analysis

Abstract: Aims: Parenting interventions in this review refer to supportive parenting training provided for parents or primary caregivers of children and adolescents with type 1 diabetes mellitus (T1DM). The review aimed to synthesize evidence about parenting interventions in parents or caregivers of children and adolescents with T1DM, and to evaluate the effect of interventions in reducing parents' or caregivers' psychological distress, helping them share diabetes management responsibility, seek social support, and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…There is a substantial literature addressing psychosocial and behavioral interventions for the treatment of children and adolescents with T1D. Systematic reviews including meta‐analyses have shown the efficacy of various approaches 198–200 including family based interventions 38,201 . While methodological limitations have been noted, 198,202–205 it can generally be concluded that there is a solid evidence base for psychosocial and behavioral interventions 206 although the effects on glycemic outcomes are inconsistent 202 .…”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
“…There is a substantial literature addressing psychosocial and behavioral interventions for the treatment of children and adolescents with T1D. Systematic reviews including meta‐analyses have shown the efficacy of various approaches 198–200 including family based interventions 38,201 . While methodological limitations have been noted, 198,202–205 it can generally be concluded that there is a solid evidence base for psychosocial and behavioral interventions 206 although the effects on glycemic outcomes are inconsistent 202 .…”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
“…Even if the parent is the central pillar of the child's life, the adult's internal psycho-emotional resources that are aimed at managing the stressful life events in diabetes mellitus are not inexhaustible. Specialists often recommend parenting interventions [24] in order to trigger new coping mechanisms and good emotional control [25,26], so that the adult's psycho-emotional state does not affect the child's quality of life. In addition, the health status of the child with T1DM and the difficulties in controlling blood glucose levels can negatively influence the family climate, generating a snowballing effect on the child's psycho-emotional climate [27].…”
Section: Introductionmentioning
confidence: 99%
“…One meta-analysis found that Parenting intervention was shown to be beneficial for parents of children with type 1 diabetes mellitus, Specifically, parenting interventions which include supportive parenting training or education programs could help parents of children with type 1 diabetes mellitus ask for positive social support (30).…”
Section: Training or Educationmentioning
confidence: 99%
“…However, the role of psychoeducational interventions on social support remains to be further explored, and extensive original research is still needed. Training or education could help increase the level of social support (30). Specifically, it focuses on helping parents of children with chronic diseases feel positively supported and providing them with practical parenting guidance, available information and resources.…”
Section: Intervention Contentmentioning
confidence: 99%
See 1 more Smart Citation